Ambipolar Triple Cation Perovskite Field Effect Transistors and Inverters. Issue 8 (5th December 2016) - Yusoff, Abd. Rashid bin Mohd.; Kim, Hyeong Pil; Li, Xiuling; Kim, Jeongmo; Jang, Jin; Nazeeruddin, Mohammad Khaja
Abstract : Ambipolar perovskite field‐effect transistors and inverters with balanced mobilities are demonstrated. Thin‐film field‐effect‐transistor‐like inverters are developed, and a maximum gain of 23 in the first quadrant for V DD = 80 V is obtained.